Antara Aktivitas Fisik dan Mental dengan Kesehatan Siswa di Sekolah: Kajian Literatur - Mauizatul Hasanah (Jurnal Kesehatan, 2024)
The importance of students‘ physical and mental health in schools is gaining widespread attention, given the variety of studies that show a close relationship between physical and mental activity and students’ general well-being. This literature review aims to analyse and synthesise findings from studies examining the impact of physical and mental activity on students' health. Research shows that physical activities, such as regular exercise and extracurricular sports, contribute significantly to improving physical health and reducing the risk of obesity, diabetes and cardiovascular disorders in students. In addition, mental activities, including mindfulness practices, psychological counselling and art activities, have been shown to strengthen mental health by reducing levels of stress, anxiety and depression. Through this literature review, enabling and constraining factors in the implementation of physical and mental activity programmes in school settings were identified. The findings can inform policy makers and educational practitioners in designing holistic interventions to improve students' overall physical and mental health in schools.